Physicochemical and microbiological characterization of leachate from the Dar El Gueddari municipal landfill Morocco - ELFAKIR, Brahim; BENZAKOUR, Abderrahim; OUHSSINE, Mohammed; LABIOUI, Hicham (Edelweiss Applied Science and Technology, 2026)
To evaluate the physicochemical and microbiological characteristics of leachate from the Dar El Gueddari public landfill and assess its environmental impact on soil, surface water and groundwater, representative samples were collected and analyzed. The leachate exhibited an alkaline pH, low dissolved oxygen concentration (1.20 mg O₂/L), high suspended solids content (790 mg/L), and high electrical conductivity (42,900 μS/cm), elevated biochemical oxygen demand (1,422 mg O₂/L) and chemical oxygen demand (4,250 mg O₂/L). High concentrations of heavy metals were detected, in particular lead (23.56 mg/L), cadmium (14.46 mg/L), arsenic (11.20 mg/L), zinc (9.80 mg/L), iron (21.68 mg/L), copper (14.74 mg/L), nickel (9.80 mg/L), and chromium (15.55 mg/L). Microbiological analyses revealed severe contamination, with total coliform counts 1.9 × 10⁶ CFU/mL at 30°C, thermotolerant coliforms at 1.7 × 10⁴ CFU/mL at 44°C, Clostridium perfringens at 3.3 × 10⁶ CFU/mL at 37°C, coagulase-positive staphylococci at 5.1 × 10⁶ CFU/100 mL, yeasts at 2.3 × 10⁶ CFU/mL, and molds at 6.5 × 10⁵ CFU/mL. The measured concentrations significantly exceed World Health Organization discharge standards, posing a serious threat to the environment and health in the Dar El Gueddari region. Consequently, appropriate treatment of the leachate before its discharge into the environment is essential.